Educational Attainment and Job Requirements: Exploring the Gaps for Construction Graduates in Australia from an Industry Point of View - Wu, Peng; Feng, Y.; Pienaar, J.; Zhong, Y. (American Society of Civil Engineers (ASCE), 2015)
© 2015 American Society of Civil Engineers. The construction industry has been facing a paradigm shift to integrate new construction requirements, most notably the development of advanced technologies, such as environmental management, information technology, and building information modeling. Timely curriculum reform is therefore necessary for construction education to adapt quickly to the paradigm shift. The aim of this paper is to investigate the gaps between educational attainment and job requirements in the Australian construction industry, based on which further curriculum reform can be conducted. A survey is administered to 252 construction graduates. The results suggest that the most significant gaps are related to technical skills for construction and problem-solving skills. The gaps can be categorized into eight groups based on an exploratory factor analysis. The eight groups are construction technology, information technology, problem-solving skills, construction economics, risk management, basic theories, business management, and sustainability science. It is therefore recommended that curriculum reform be conducted to bridge the gaps between educational attainment and job requirements to prepare construction graduates for the competitive and fast-changing construction environment.